Hydrocarbon chemistry in the atmosphere of a Warmer Exo-Titan - Adams, Danica; Luo, Yangcheng; Yung, Yuk L. (Frontiers in Astronomy and Space Sciences, 2022)
Hosting a ~1.5 bar N2 atmosphere and reducing atmospheric composition, Titan has the energy sources needed to drive disequilibrium chemistry and hosts an aerosol layer which shields the surface from incident UV radiation. This world draws parallels to an early Earth-like world (although ~200 K cooler), and the atmospheric chemistry may be capable of forming relevant prebiotic species. Exo-Titan worlds at close-in orbits host photochemistry relevant to habitability with rich hydrocarbon chemistry. We investigate the effect of stellar type of the host star, equilibrium temperature, incident radiation, and vertical transport efficiency on the production of higher-order hydrocarbons. We find a greater incident radiation (a closer orbit) increases the rate of methane photolysis as well as photolysis of hydrocarbons. A larger H2 abundance and warmer temperature increases the rate of the back reaction H2 + CH3 -> CH4 + H, and the temperature dependence is so great that CH3 recycles back into CH4 instead of forming C2H6. A larger H2 abundance and warmer temperature also encourages interesting cycling between C2H2, C2H3, and C2H4 via reactions with atomic H.